ANALISIS YURIDIS PENERAPAN PRINSIP BEST PRACTICES DIGITAL FORENSICS DALAM MENJAMIN KEABSAHAN ALAT BUKTI ELEKTRONIK DI INDONESIA - Alif Nur Azis; Sunariyo Sunariyo; Bayu Prasetyo (LPPM STIH Awang Long, 2026)
Digital transformation has altered criminal behavior and evidentiary practices in the modern criminal justice system, particularly in cases involving cybercrime and technology-based offenses. Electronic information and electronic documents are increasingly used as evidence, yet their admissibility in court cannot rely solely on formal legal recognition; it is also determined by their authenticity, integrity, reliability, and a verifiable chain of custody. The urgency of this research is driven by the inherent nature of electronic evidence, which is easily altered, copied, transferred, manipulated, and even deleted without leaving easily identifiable traces. These conditions demand adequate legal and technical standards to ensure that electronic evidence can be accepted and evaluated objectively at trial. The purpose of this research is to analyze the admissibility of electronic evidence in the Indonesian criminal justice system, compare it with the evidentiary framework in the United States, and examine the relevance of implementing international digital forensics best practices to strengthen the admissibility of electronic evidence in Indonesia. This study employs normative legal research methods with statutory, conceptual, and comparative approaches. The research analysis is grounded in the theory of evidence and the theory of digital forensics best practices. Both theories are used consistently as an analytical framework to examine the compatibility between the normative recognition of electronic evidence and the technical digital forensics standards required in criminal evidence. The primary legal materials used include Law Number 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions Law, Law Number 20 of 2025 concerning the Criminal Procedure Code, Law Number 1 of 2023 concerning the Criminal Code, ISO/IEC 27037:2012, NIST Special Publication 800-86, and the Federal Rules of Evidence. The research gap lies in the fact that while Indonesian law normatively recognizes electronic evidence, it has not yet provided uniform technical procedures regarding the acquisition, preservation, authentication, forensic analysis, and presentation of electronic evidence in court. Based on the conducted research, it is established that the ITE Law and the Criminal Procedure Code have recognized electronic evidence as valid evidence, but the regulations remain predominantly normative and lack uniform technical procedures. This contrast with the United States, which possesses more detailed evidentiary parameters through principles of authentication, relevance, the best evidence rule, self-authentication, hearsay exceptions, and expert testimony based on the Daubert standard. This study concludes that the admissibility of electronic evidence in Indonesia requires harmonization between legal norms and forensic technical standards, specifically through the implementation of ISO/IEC 27037 and NIST SP 800-86 to guarantee authenticity, integrity, chain of custody, reliability, legal certainty, and accountability at every stage of digital evidence handling.